The cruise of the Alabama and the Sumter - Semmes, Raphael, 1809-1877 (Carleton, 1864)
First published over 100 years ago, CRUISE OF THE ALABAMA AND THE SUMTER is Raphael Semmes? incredible story of his experiences as a commander in the Confederate Navy during the Civil War. Semmes draws upon his private journals and papers to unfold his memories of capturing merchant vessels and skillfully eluding Union warships while commanding both the Alabama and Sumter. Together with his crew, Semmes endured a career of commerce raiding that was without equal in American naval history of its time.